Reformacijska gibanja v okviru evropskega 16. stoletja - Štuhec, Marko (Slavia Centralis, 2020)
The Reformation in 16th Century Europe. The European reformations emerged in the religious, social, cultural and political context of the long 16th century. This period is char-acterized by specific intertwining of pre-modern and medieval elements such as the predominance of the agrarian economy and the rural world, the dynastic foundation of politics, the society of orders and Christianity, and early modern, sometimes even modern elements such as print, economic and demographic growth, high conflict potential, the emergence of the early modern state, and European expansion. On the one hand, the complex of the new and the old structural elements influenced the shaping, spread, reception and affirmation or defeat of various types of the reformation; on the other hand, there were Reformation ideas and movements which the author defines as large scale sociopsychological interactions, with their own dyna-mism which contributed to the change of the existing structures.